2016
DOI: 10.21103/article6(4)_oa3
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Receptor FokI Gene Polymorphism Predicted Poor Response to Treatment in Chronic HCV Genotype 4

Abstract: The aim of this study was to investigate the association between a genetic polymorphism of the vitamin D receptor (VDR) and antiviral responses in Egyptian patients with chronic hepatitis C virus genotype 4 (HCV-4). Methods: Our study enrolled 100 HCV-4 patients who received pegylated interferon alpha-2a (pegIFNα-2a) and ribavirin for 48 weeks. Patients were divided into 2 groups according to their response to therapy: 50 were responders, and 50 were nonresponders. All HCV-4 patients were further subjected to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 29 publications
(49 reference statements)
0
3
1
Order By: Relevance
“…Regarding VDR and DBP genes polymorphisms in Brazilian population, the BsmI, ApaI, TaqI, and the rs4588 and rs7041 polymorphisms were most consistently associated with lower 25 (OH)D levels. [ 26 , 40 ] However, in the present study both SNPs were not associated with lower levels of 25 (OH)D after applying Bonferroni correction. Nevertheless, Falleti et al [ 16 ] demonstrated that normal serum vitamin D levels and the carriage of GC-globulin WT isoform strongly predict the achievement of SVR after PEG-interferon plus RBV antiviral therapy.…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…Regarding VDR and DBP genes polymorphisms in Brazilian population, the BsmI, ApaI, TaqI, and the rs4588 and rs7041 polymorphisms were most consistently associated with lower 25 (OH)D levels. [ 26 , 40 ] However, in the present study both SNPs were not associated with lower levels of 25 (OH)D after applying Bonferroni correction. Nevertheless, Falleti et al [ 16 ] demonstrated that normal serum vitamin D levels and the carriage of GC-globulin WT isoform strongly predict the achievement of SVR after PEG-interferon plus RBV antiviral therapy.…”
Section: Discussioncontrasting
confidence: 71%
“…This way, FokI C>T polymorphisms may be used as a molecular marker to predict the risk and to evaluate the disease severity of HCC in those infected with HCV since low concentrations of vitamin D is directly associated with increased liver injury in Brazilian population. Differently, Shehab et al [ 40 ] observed that VDR genetic polymorphisms are significantly associated with the occurrence of HCV-related HCC especially T allele carriers which could be considered as a risk factor of hepatocellular carcinoma in Egyptian patients.…”
Section: Discussionmentioning
confidence: 99%
“…In DBP gene polymorphisms in other populations, rs4588 and rs7041 polymorphisms were most consistently associated with lower 25 (OH)D levels [19][20][21][22][23]. There are also other variants of GC, namely, rs16846876, rs17467825, rs2282679, rs3755967, rs2298850, and rs1155563, which were reported to be significantly associated with both 25(OH)D concentrations and vitamin D deficiency (25(OH)D < 15 ng/mL) [24].…”
Section: Discussionmentioning
confidence: 94%
“…There are controversial data claiming that the differences in total 25(OH)D among populations or ethnicities depend on the derivation of free 25(OH)D using results obtained from a monoclonal assay for calculating DBP concentration [23]. Nielson et al showed that the monoclonal ELISA underestimates DBP concentrations in individuals with GC/1f alleles [32].…”
Section: Discussionmentioning
confidence: 99%